2009
DOI: 10.1158/1535-7163.mct-09-0274
|View full text |Cite
|
Sign up to set email alerts
|

Increased antitumor activity of bevacizumab in combination with hypoxia inducible factor-1 inhibition

Abstract: Inhibition of hypoxia inducible factor-1 (HIF-1) is an attractive therapeutic strategy to target the tumor microenvironment. However, HIF-1 inhibitors may have limited activity as single agents and combination therapies may be required. We tested the hypothesis that HIF-1 inhibition in a hypoxic-stressed tumor microenvironment, which could be generated by administration of antiangiogenic agents, may result in a more pronounced therapeutic effect. The activity of bevacizumab, either alone or in combination with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(116 citation statements)
references
References 33 publications
6
109
0
1
Order By: Relevance
“…We investigated the effect on metastasis formation of sunitinib with topotecan administered daily at suboptimal doses, previously reported to affect the hypoxic tumor microenvironment (34,35).…”
Section: The Increase In Metastases Due To Sunitinib Depends On Tumormentioning
confidence: 99%
“…We investigated the effect on metastasis formation of sunitinib with topotecan administered daily at suboptimal doses, previously reported to affect the hypoxic tumor microenvironment (34,35).…”
Section: The Increase In Metastases Due To Sunitinib Depends On Tumormentioning
confidence: 99%
“…Unexpectedly, we detected a gradual decrease in HIF reporter activity over the duration of bevacizumab treatment. In the few publications that evaluated the effect of bevacizumab using a luminescent HIF reporter results were divergent: activation of the reporter in a lung adenocarcinoma model (15) and inhibition of the reporter in a glioblastoma model (16). A decrease in HIF reporter activity by antiangiogenic treatment could be explained by: i) a decrease in intratumoral hypoxia caused by vascular normalization; ii) an increase in intratumoral hypoxia that may cause a decrease in luciferase activity due to limited oxygen availability; iii) reduced availability of luciferase substrate as a consequence of reduced vascularization; and iv) an increase in intratumoral hypoxia compensated with a decrease in the number of viable cells.…”
Section: Discussionmentioning
confidence: 99%
“…We used the 9xHRE-luciferase (9xHRE-luc) reporter vector that harbors nine copies of the HRE derived from the VEGFA gene upstream of a minimal rat prolactin promoter driving the expression of the firefly luciferase gene (12). Similar vectors, containing a variable number of HREs and diverse reporter genes (luciferase or EGFP) have been developed and used as functional reporters for optical imaging over the last 5 years (13)(14)(15)(16)(17)(18)(19). Hypoxic conditions lead to hypoxia inducible factor (HIF) stabilization and subsequent induction of luciferase reporter gene expression through binding of HIF to HREs in the reporter and activation of transcription driven by HIF.…”
Section: In Vitro Functional Evaluation Of 9xhre-luciferase Reporter mentioning
confidence: 99%
“…This strategy provided superior anti-angiogenic effects, which also resulted in superior anti-tumour activity in a glioblastoma xenograft model. 3,121 Another remarkable preclinical study was performed by Kerbel and colleagues at the University of Toronto. They demonstrated that combining pazopanib (Votrient s ; GlaxoSmithKline), a VEGF receptor inhibitor, with metronomic TPT, is synergistic and resulted in 100% survival of the drug combination (but not the individual monotherapies) after 6 months of continuous therapy in an aggressive, metastatic, orthotropic xenograft ovarian model.…”
Section: Combination Therapymentioning
confidence: 99%